IMPACT OF NEEDS ON SOCIO-ECONOMIC DEVELOPMENT of the state - S. Vikulov (Вестник университета)
In the modern world the level of living in the state, as a rule, is defined by the level of social and economic development. In article the description of social and economic development, a level of living and needs of the state is given. Influence of requirements on social and economic development of the state is considered and conclusions about interrelation of requirements and social and economic development of the state are drawn. The author pays special attention to interrelation of net income as indicator of social and economic development and requirements, noting cyclic interrelation between growth of the income and growth of needs of separately taken person.